Habitat Use by Changeable hawk-eagle, Crested serpent-eagle and White bellied sea-eagle at Nature Recreation Park of Lake Buyan and Lake Tamblingan and Surrounding Area - Rohman, Fathur; Ginantra, I Ketut; Dalem, Anak Agung Gde Raka (Metamorfosa: Journal of Biological Sciences; Vol 6 No 1 (2019), 2019)
Research on the habitat preferrence by Changeable hawk-eagle ( Nisaetus cirrhatus) (CHE), Crested serpent-eagle ( Spilornis cheela ) (CSE), and White bellied sea-eagle ( Haliaeetus leucogaster) (WSE) was conducted at Nature Recreation Park of Lake Buyan and Lake Tamblingan and Surrounding area between February and July, 2016. Data collection was conducted through field observation using the “look down method” and the “look up method” combined with placement of observation points. Data collection was analysed by principle component analisys (PCA) method. Research results related to preferenced habitat were as follows: (1) the CHE prefered fragmented forest, secondary forest, and cultivated forest types habitat. (2) The CSE prefered habitat types of farming land, residence, and sosial forest. (3) The WSE prefered just one habitat type, that was the wet land habitat type. Keywords: eagle, raptor,  forest, habitat, habitat preference, bali